The Eradication of Human Trafficking: What Can We Learn From East Lombok District? - Ika Yuliana Susilawati; Sri Karyati; Hafizatul Ulum (Magister of Law, Faculty of Law, University of Mataram, 2024)
The lack of information regarding labor migration in the society of West Nusa Tenggara Province means that quite few prospective Indonesian Migrant Workers (IMW) are vulnerable to malpractice recruitment and can result in exploitation so that they have the potential to become human trafficking victims. This study aimed to determine the effectiveness of West Nusa Tenggara Provincial Regulation Number 10 of 2008 and the obstacles and also the opportunities for preventing and eradicating human trafficking as an effort to prevent human trafficking in East Lombok Regency. The results of this study that are West Nusa Tenggara Provincial Regulation Number 10 of 2008 concerning Prevention and Eradication of Human Trafficking and its derivative, namely East Lombok Regency Regional Regulation Number 9 of 2013 concerning Protection of Victims of Human Trafficking and Acts of Violence against Women and Children are not running effectively considering that the mandate of these two regional regulations is to form a Cluster Human Trafficking duties at the Regency Level have not been carried out, so that the relevant agencies cannot coordinate optimally. Optimizing the Eradication of Human Trafficking in East Lombok Regency can be done by forming a Human Trafficking Task Force so that inter-agency cooperation can run optimally. The formation of the Human Trafficking Task Force will provide certainty regarding the involvement of human resources, funding and facilities and infrastructure. Apart from the role of the Human Trafficking Task Force, of course there is also a need for public awareness, especially prospective migrant workers, to register themselves legally so that they can prevent them from becoming victims of Human Trafficking.